Empire and elites after the Muslim conquest the transformation of northern Mesopotamia - Robinson, Chase F. (Cambridge studies in Islamic civilization, 2006)
First published in 2000, Chase Robinson's book takes account of the research available in early Islamic history, interweaving history and historiography to interpret the political, social and economic transformations in the Mesopotamian region after the Islamic conquests. This is a sophisticated study in a burgeoning field in Islamic studies.